me explica melhor essa equaçao 2(x+1)-3(2x-5)=6x-3
Soluções para a tarefa
Respondido por
0
2(x + 1) - 3(2x - 5) = 6x - 3
2x + 2 - 6x + 15 = 6x - 3
2x - 6x - 6x = -3 - 15 - 2
2x - 12x = -20
-10x = -20 (multiplicando ambos os lados por -1)
10x = 20
x = 20/10
x = 2
Resposta: x = 2
Espero ter ajudado.
2x + 2 - 6x + 15 = 6x - 3
2x - 6x - 6x = -3 - 15 - 2
2x - 12x = -20
-10x = -20 (multiplicando ambos os lados por -1)
10x = 20
x = 20/10
x = 2
Resposta: x = 2
Espero ter ajudado.
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Artes,
1 ano atrás